2005
DOI: 10.1534/genetics.104.037176
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Meiotic DNA Break Site in Schizosaccharomyces pombe Is a Hotspot of Gene Conversion, Highly Associated With Crossing Over

Abstract: In Schizosaccharomyces pombe, meiosis-specific DNA breaks that initiate recombination are observed at prominent but widely separated sites. We investigated the relationship between breakage and recombination at one of these sites, the mbs1 locus on chromosome I. Breaks corresponding to 10% of chromatids were mapped to four clusters spread over a 2.1-kb region. Gene conversion of markers within the clusters occurred in 11% of tetrads (3% of meiotic chromatids), making mbs1 a conversion hotspot when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
78
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 48 publications
10
78
0
2
Order By: Relevance
“…If conversions at ade6 occurred without high levels of associated crossing over, this observation could be accounted for; i.e., rec10-155 is defective in the conversions at ade6 that have little associated crossing over. However, Cromie et al (2005) recently demonstrated that there are high levels of crossovers associated with conversions at ade6, dismissing the proposal that there is a greater reduction in conversions at ade6 than crossovers in the rec10-155 mutant because there is limited crossing over associated with ade6 gene conversions. A similar, but less dramatic, observation has also been made for mutants defective in the meiosis-specific cyclin Rem1, where a reduction in gene conversions is observed ($4-fold) at ade6, but no reduction in crossing over in the adjacent ade6-arg1 interval (Malapeira et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…If conversions at ade6 occurred without high levels of associated crossing over, this observation could be accounted for; i.e., rec10-155 is defective in the conversions at ade6 that have little associated crossing over. However, Cromie et al (2005) recently demonstrated that there are high levels of crossovers associated with conversions at ade6, dismissing the proposal that there is a greater reduction in conversions at ade6 than crossovers in the rec10-155 mutant because there is limited crossing over associated with ade6 gene conversions. A similar, but less dramatic, observation has also been made for mutants defective in the meiosis-specific cyclin Rem1, where a reduction in gene conversions is observed ($4-fold) at ade6, but no reduction in crossing over in the adjacent ade6-arg1 interval (Malapeira et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hotspots in yeast (Malone et al 1994;Wu and Lichten 1995;Petes 2001;Cromie et al 2005), mice (Guillon and De Massy 2002;Kelmenson et al 2005;Shifman et al 2006;Baudat and De Massy 2007), and humans ( Jeffreys et al 1998( Jeffreys et al , 2000( Jeffreys et al , 2001Crawford et al 2004;McVean et al 2004;Myers et al 2005;Conrad et al 2006;International HapMap Consortium 2007) have now been well characterized, and evidence suggests that hotspots also exist in chimpanzees (Ptak et al 2005) and several plants (Dooner and Martinez-Ferez 1997;Okagaki and Weil 1997;Yao et al 2002;Drouaud et al 2006). While some other well-studied eukaryotes (e.g., Drosophila melanogaster and Caenorhabditis elegans) show no evidence of hotspots (Hey 2004), the phenomenon is widespread enough across the tree of life to merit substantial study.…”
mentioning
confidence: 99%
“…One striking characteristic of hotspots is that they are subject to a form of meiotic drive: when a DSB occurs at a hotspot heterozygous for an active (''hot'') and an inactive (''cold'') hotspot allele, the cold allele tends to appear in a higher proportion of the offspring than does the hot allele (often in an $3:1 ratio rather than the expected 2:2) (Catcheside 1975;Nicolas et al 1989;Grimm et al 1991;Malone et al 1994;Guillon and De Massy 2002;Jeffreys and Neumann 2002;Jeffreys and May 2004;Cromie et al 2005). This is likely the result of the mechanism by which recombination is thought to be initiated: a doublestrand break (DSB) forms on one chromatid; this break extends a variable distance in the 59 direction on each strand; and the sequence of the nonsister chromatid is used as a template to repair the gap.…”
mentioning
confidence: 99%
“…Additionally, to explain the negative interference between ade6 1 convertants and tps16-arg1 crossovers (Table 2), the frequency of conversion at tps16 would have to be at least 17%, but only among ade6 1 spores. Gene conversion in S. pombe meiosis is frequently associated with crossing over between flanking markers (Grimm et al 1994;Cromie et al 2005). Negative interference between a conversion and a crossover could be explained if the conversion and crossover were not separate events.…”
Section: Discussionmentioning
confidence: 99%
“…In meiosis, unlike mitosis, gene conversion is frequently associated with crossing over (Grimm et al 1994;Virgin et al 2001;Cromie et al 2005 and references therein). Consequently, the recombination events that occasionally occur between dispersed repetitive DNA, such as transposons, genes for tRNAs, subtelomeric sequences, and multigene families, may frequently involve crossovers.…”
mentioning
confidence: 99%